The Production Process of Oysters (Cassostrea gigas) for High Quality Products in the Sakoshi Fishermen's Group, Ako, Japan - Muhamad Luthfi Az-Zakiy; Junianto Junianto (Universitas Islam Lamongan, 2024)
Pacific oysters can be marketed either dead or alive with their shells (karatsuki), which are known for their high quality due to their ability to retain moisture, natural flavor, and luxurious appeal. This study examines the production process of oysters by fishermen in Sakoshi Bay, Ako, utilizing precise methods from cleaning, sorting, storing, to packaging. Observation and interview methods were used to obtain data on the production process. The results show that processing according to standards and the skilled experience of Sakoshi fishermen maintain the quality of the oysters. The combination of modern technology and traditional knowledge provides a competitive advantage. This research emphasizes the importance of proper production methods in maintaining the quality of fishery products and offers insights into best practices that other producers can adopt.